Eragon - Paolini, Christopher (Paolini, Christopher. Inheritance (Alfred A. Knopf, Inc.), 2003)
In Aagaesia, a fifteen-year-old boy of unknown lineage called Eragon finds a mysterious stone that weaves his life into an intricate tapestry of destiny, magic, and power, peopled with dragons, elves, and monsters.